Lithium manganese iron phosphate positive electrode material and preparation method thereof

By controlling the solid content and feeding sequence of the precursor slurry, and adding organic phosphine-based scale-repelling corrosion inhibitor after grinding, the conductivity and cycle stability of lithium manganese iron phosphate positive electrode material is solved, and a high-performance positive electrode material preparation is achieved.

CN119911889APending Publication Date: 2025-05-02WANHUA CHEMICAL (YANTAI) BATTERY MATERIAL SCIENCE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311421165.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Lithium manganese iron phosphate positive electrode material has problems such as poor electron and ion conductivity, low discharge capacity and fast cycle attenuation, which limits its application in lithium-ion batteries.

Method used

By controlling the solid content and feeding sequence of the precursor slurry, performing a grinding and adding an organic phosphine-based scale-resisting corrosion inhibitor thereafter, it is preferred to perform a secondary grinding treatment to form a stable soluble complex, improving the stability and electrochemical properties of the slurry.

Benefits of technology

The high electron and ion conductivity, high discharge capacity and good cycle stability of lithium manganese iron phosphate cathode material are achieved, improving its performance in lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a lithium manganese iron phosphate positive electrode material and a preparation method thereof, and the preparation method comprises the following steps: (1) uniformly stirring an iron source, a phosphorus source, a lithium source and a dispersant in water, adding a manganese source, and uniformly mixing to obtain precursor prefabricated slurry; (2) adjusting the solid content of the precursor prefabricated slurry to reach a target solid content A, wherein the target solid content A is more than or equal to 30wt% and less than or equal to 60wt%; (3) carrying out primary grinding treatment on the precursor slurry obtained in the step (2); and (4) adding an organic phosphine scale and corrosion inhibitor into the precursor slurry, dissolving, drying the obtained slurry, sintering, and crushing to obtain the lithium iron manganese phosphate positive electrode material. Wherein the carbon source is added and dissolved in the step (1), or the carbon source is added and dissolved in the precursor slurry in the step (4). By adopting the method disclosed by the invention, the positive electrode material with relatively good electrochemical properties such as discharge capacity and rate capability can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of lithium ion battery positive electrode materials, and specifically relates to a preparation method and application of a high-capacity and high-density lithium manganese iron phosphate positive electrode material. Background Art

[0002] Lithium-ion batteries have become the most widely used energy storage method in today's society due to their high energy density, environmental protection, and long cycle life. They are widely used in electric vehicles, consumer electronics, and energy storage systems. However, it is still a challenge to manufacture low-cost, high-energy-density, and long-cycle-life lithium-ion batteries. The performance of the battery mainly depends on the positive electrode material. The positive electrode materials currently widely used in the market include lithium cobalt oxide, lithium manganese oxide, nickel-cobalt-manganese ternary materials, and lithium iron phosphate. Among them, lithium iron phosphate positive electrode materials are gaining more and more market share due to their long cycle life, high stability, low cost, and abundant raw material sources, especially in electric vehicles and energy storage systems.

[0003] However, a major problem with lithium iron phosphate is that its discharge voltage is relatively low, which limits the energy density of the battery. In contrast, lithium manganese phosphate has a higher discharge voltage platform at the same specific capacity, and therefore has a higher theoretical energy density. However, the electronic and ionic conductivity of lithium manganese phosphate is extremely poor, and because of the Günther effect, the capacity will gradually decay during the battery charge and discharge cycle, resulting in a short cycle life and cannot be used in practice. The manganese / iron elements in lithium manganese iron phosphate can be mutually dissolved in any proportion to form an olivine structured solid solution. It combines the structural stability of lithium iron phosphate with the high voltage of lithium manganese phosphate, with a higher voltage platform than lithium iron phosphate, and excellent low-temperature performance, and is expected to be used as a positive electrode material with higher energy density in lithium-ion batteries. However, compared with lithium iron phosphate, lithium manganese iron phosphate currently still has problems such as low electronic / ionic conductivity, low discharge capacity, and faster cycle decay that need to be solved urgently. In the process of production practice, it was found that the main factors currently limiting the performance of lithium manganese iron phosphate are the poor uniformity of the precursor slurry system and particle size, which easily leads to sedimentation and causes system inhomogeneity, resulting in uneven distribution of precursor components obtained by spraying and poor capacity of lithium manganese iron phosphate obtained by sintering. Summary of the invention

[0004] To solve the above problems, the present invention provides a lithium iron manganese phosphate positive electrode material and a preparation method thereof, which solves the problems of low electronic conductivity and ion conductivity, low discharge capacity and fast cycle decay of the lithium iron manganese phosphate material.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing a lithium manganese iron phosphate positive electrode material comprises the following steps:

[0007] (1) After the iron source, phosphorus source, lithium source and dispersant are uniformly stirred in water, a manganese source is added, and the mixture is uniformly mixed to obtain a precursor pre-slurry; specifically, for example, step (1) is performed in a stirring tank, water is added first, and then other materials are added;

[0008] (2) adjusting the solid content of the precursor pre-slurry to reach a target solid content A, wherein the target solid content A satisfies 30%≤A≤60%, preferably 35%≤A≤50%; preferably, the solid content of the precursor pre-slurry is adjusted by adding water; preferably, the volume percentage of water used in step (1) to the total volume percentage of water used in step (1) and step (2) is 85-99%, for example 85%, 88%, 90%, 92%, 94%, 97%, 99%, etc., for example 85-97%;

[0009] (3) grinding the precursor slurry obtained in step (2) under stirring;

[0010] (4) adding an organic phosphine scale inhibitor to the precursor slurry obtained in step (3) to dissolve the precursor slurry, preferably performing a secondary grinding treatment, and then drying the obtained slurry, sintering and pulverizing to obtain a lithium manganese iron phosphate positive electrode material;

[0011] The carbon source is added and dissolved in step (1), or the carbon source is added and dissolved in the precursor slurry in step (4). That is, the carbon source can be added in step (1) or in step (4). For example, in step (4), the carbon source and the organic phosphine scale inhibitor are added to the precursor slurry and stirred until they are completely dissolved.

[0012] In the present invention, by controlling the solid content of the precursor slurry, grinding once, and then adding the organic phosphine scale inhibitor, according to a specific order of adding materials, it is beneficial to obtain a slurry with better stability, to obtain a positive electrode material with higher compaction density, and to obtain a positive electrode material with better electrochemical properties such as discharge capacity and rate performance. More preferably, a secondary grinding treatment is performed after adding the organic phosphine scale inhibitor, and the complexing, solubilizing and dispersing effects of the organic phosphine scale inhibitor can be used to form a stable soluble complex with metal ions or oxides, further improve the slurry stability, and inhibit slurry precipitation and precipitation; it can further improve the compaction density of the positive electrode material, and improve the electrochemical properties such as discharge capacity and rate performance.

[0013] The present inventors have found that, compared with adding the organic phosphine scale inhibitor before the first grinding (e.g., in step (1)), adding the organic phosphine scale inhibitor after the first grinding can prevent the organic phosphine scale inhibitor from reacting with the alkaline substances in the raw materials and becoming inactivated, thereby effectively exerting its complexing, solubilizing and dispersing effects.

[0014] Preferably, in step (1) of the present invention, the iron source is selected from one or more of iron oxide, ferroferric oxide, ferrous phosphate, ferrous oxalate, and ammonium ferrous phosphate; the phosphorus source is one or more of ferric phosphate, phosphoric acid, lithium dihydrogen phosphate, manganese hydrogen phosphate, and ammonium dihydrogen phosphate; the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate; the dispersant is one or more of polyethylene glycol 800, polyethylene glycol 6000, methyl cellulose, polyvinyl alcohol, and hexenyl bisstearamide; the manganese source is one or more of manganese dioxide, manganese carbonate, manganese oxalate, manganese sulfate, manganese tetraoxide, and manganese hydrogen phosphate;

[0015] Preferably, the molar ratio of iron element to manganese element is 0.11-1:1, and the ratio of the molar amount of lithium element added to the sum of the molar amounts of iron element and manganese element added is 0.9-1.1:1; the above iron element, manganese element and lithium element refer to the corresponding elements contained in the raw materials added during the preparation of the slurry.

[0016] Preferably, based on the volume of water added in step (1), the amount of the dispersant added is 5-50 g / L, for example, 5 g / L, 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, etc., preferably 10-35 g / L; the preferred dispersant concentration is used to further improve the uniformity of the precursor slurry, so that the slurry is evenly distributed and the particles are of uniform size, which is conducive to finally obtaining a lithium manganese iron phosphate positive electrode material with better electrochemical performance.

[0017] Preferably, in step (3) of the present invention, the precursor slurry is subjected to the aforementioned primary grinding treatment to a particle size D50 of 0.35-0.55 nm, preferably 0.4-0.45 μm; the particle size of the slurry after the primary grinding is controlled within a preferred range, which is beneficial to further improve the uniformity of the precursor slurry, make the slurry evenly distributed, and make the particles of uniform size, which is beneficial to ultimately obtain a lithium manganese iron phosphate positive electrode material with better electrochemical performance.

[0018] Preferably, the ratio of the sum of the molar amounts of phosphorus in the phosphorus source used in step (1) and the organic phosphine scale and corrosion inhibitor used in step (4) of the present invention to the sum of the molar amounts of iron and manganese in the manganese source and the iron source is p (i.e., P element: (Fe element + Mn element), molar ratio), 0.99≤p≤1.05;

[0019] Preferably, based on the volume of water used in step (1), the amount of organic phosphine scale inhibitor added is 0.02-0.4 mol / L, preferably 0.04-0.2 mol / L. The preferred amount of organic phosphine scale inhibitor added is conducive to further improving the uniformity of the slurry and further improving the electrochemical performance of the lithium manganese iron phosphate positive electrode material.

[0020] The organic phosphine scale inhibitor contains more than two phosphonic acid groups, and the phosphorus atom is directly connected to the carbon atom. Preferably, the organic phosphine scale inhibitor includes one or more of hydroxyethylidene diphosphonic acid, aminotrimethylene phosphonic acid, diethylenetriamine penta (methylene phosphonic acid), and ethylenediaminetetramethylene phosphonic acid.

[0021] Preferably, the carbon source includes one or more of glucose, sucrose, ascorbic acid, and starch;

[0022] Preferably, based on the volume of water added in step (1), the amount of the carbon source added is 10-80 g / L, preferably 20-50 g / L;

[0023] Preferably, in step (4) of the present invention, after the organic phosphine scale inhibitor is added and dissolved, the viscosity of the obtained slurry is 100-1000 Pa·s, preferably 200-600 Pa·s. The slurry with the above preferred viscosity obtained by the preparation method of the present invention has better uniformity and is not prone to sedimentation.

[0024] Preferably, in step (4) of the present invention, the secondary grinding treatment is performed, and the particle distribution uniformity coefficient b in the obtained slurry is less than 0.3, preferably less than 0.2;

[0025] Preferably, in step (4) of the present invention, the drying is carried out by spray drying, and the spray drying air inlet temperature is controlled to be 240-280°C, preferably 250-270°C; the air outlet temperature is 85-105°C, preferably 90-100°C;

[0026] Preferably, in step (4) of the present invention, the dried precursor is sintered in a nitrogen atmosphere, and the sintering conditions are preferably: heating to 250-350°C at a heating rate of 2-5°C / min, keeping warm for 1-3h, then heating to 400-550°C at a heating rate of 2-5°C / min, keeping warm for 1-3h, then heating to the target temperature at a heating rate of 2-5°C / min, keeping warm for 5-12h. The target temperature is set to 600-800°C, preferably 650-750°C.

[0027] The present invention also provides a lithium iron manganese phosphate positive electrode material prepared by the preparation method of the lithium iron manganese phosphate positive electrode material; the chemical formula of the lithium iron manganese phosphate positive electrode material is preferably Li x Mn y Fe z (PO4) p , where 0.9≤x≤1.1, 0.5≤y≤0.9, 0.1≤z≤0.5, 0.99≤p≤1.05, and y+z=1.

[0028] In the present invention, the lithium manganese iron phosphate positive electrode material prepared by the above preparation method has the characteristics of high electronic conductivity and ionic conductivity, small and uniform particle size, low manganese dissolution and iron dissolution rate, and stable structure. The positive electrode material is applied to lithium-ion batteries to improve discharge capacity, rate performance and long cycle life.

[0029] In the present invention, an organic phosphine scale inhibitor is added to the slurry after the first grinding, and preferably a second sand grinding treatment is performed. The organic phosphine scale inhibitor can form a stable soluble complex with metal ions or oxides by utilizing the complexing, solubilizing and dispersing effects of the organic phosphine scale inhibitor, thereby increasing the slurry stability and inhibiting the precipitation and precipitation of the slurry.

[0030] During the high-temperature sintering process, the phosphorus oxygen groups of the organic phosphine scale inhibitors provide additional phosphate groups, which combine with Mn and Fe ions to form lithium iron manganese phosphate. At the same time, due to the chelation between the organic phosphine scale inhibitors and metal cations, and the in-situ carbon directly generated on the phosphorus oxygen tetrahedron after high-temperature decomposition, the mass transfer process of lithium iron manganese phosphate during the sintering process is hindered, the irregular growth of lithium iron manganese phosphate is inhibited, and small particles of lithium iron manganese phosphate are generated. The graphitized carbon layers produced by these decompositions make the small particles of lithium iron manganese phosphate bonded into secondary agglomerates. The lithium iron manganese phosphate obtained by this method has a small and uniform particle size. At the same time, due to the presence of secondary agglomerates, the compaction density is improved, and high-capacity and high-density lithium iron manganese phosphate is obtained. The obtained lithium iron manganese phosphate positive electrode material has better electrochemical properties and improved discharge capacity and rate performance.

[0031] The present invention controls the solid content and the order of adding the precursor slurry, and adds an organic phosphine scale inhibitor after the first grinding treatment, and preferably continues the second grinding, so as to obtain a precursor slurry with better uniformity. More preferably, the concentration of the dispersant, the viscosity of the slurry and the sand grinding particle size are further controlled within a preferred range, so as to further improve the uniformity of the precursor slurry, so that the slurry is evenly distributed and the particles are of the same size. The preparation method of the present invention can obtain a positive electrode material with a high compaction density, and the positive electrode material has improved electrochemical properties such as discharge capacity and rate performance. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below in conjunction with specific embodiments. The embodiments provide specific implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following embodiments.

[0033] Ingredients Description:

[0034] Iron oxide (purity ≥ 98%), manganese tetraoxide (purity ≥ 98%), lithium hydroxide (purity ≥ 99%), phosphoric acid (purity ≥ 85%), ammonium dihydrogen phosphate (analytical grade), polyethylene glycol 800, polyvinyl alcohol, polyethylene glycol 6000, sucrose (purity 99%), ascorbic acid (purity 99%) and starch: the manufacturer is Beijing Inokai Technology Co., Ltd.

[0035] Ferric phosphate (purity ≥ 99%), manganese carbonate (analytical grade), methyl cellulose, glucose, diethylenetriamine penta (methylene phosphonic acid) (50 wt % aqueous solution), hydroxyethylidene diphosphonic acid (60 wt % aqueous solution), ethylenediamine tetramethylene phosphonic acid (purity 95%): the manufacturer is Aladdin Biochemical Technology Co., Ltd.

[0036] Ferrous oxalate (purity ≥ 96%), manganese oxalate (purity ≥ 99%): the manufacturer is Shanghai McLean Biochemical Technology Co., Ltd.;

[0037] Lithium carbonate and lithium dihydrogen phosphate: analytical grade, Sinopharm Chemical Reagent Co., Ltd.;

[0038] Ammonium ferrous phosphate: homemade;

[0039] Aminotrimethylenephosphonic acid: purity 99%, Jining Huipeng Chemical Co., Ltd.

[0040] Description of the test method:

[0041] Sand-grinding slurry particle size D50 and particle distribution uniformity coefficient b in the sand-grinding slurry: The material discharged from the sand mill outlet was tested using a Malvern 3000 laser particle size analyzer.

[0042] Slurry viscosity: Take the slurry at the outlet of the sand mill for viscosity test using a Brookfield DV2T viscometer.

[0043] Powder compaction density: Take the finished product after air flow crushing for powder compaction density test, use Sansi UTM7305 compaction density meter to test, the test pressure is 3T.

[0044] The content of each element in the prepared positive electrode material was determined by ICP test.

[0045] Electrochemical performance test: The sample material was mixed with the binder PTFE (polytetrafluoroethylene) and the conductive carbon black in a mass ratio of 9:0.5:0.5 and ground evenly in an agate mortar to obtain a slurry. The slurry was evenly coated on the aluminum foil, and the positive electrode was cut after vacuum drying. The lithium sheet was used as the negative electrode, the diaphragm was Celgard2400, and the 1mol / L LiPF6 solution (the solvent was EC (ethylene carbonate), DEC (diethyl carbonate) and DMC (dimethyl carbonate) in a mass ratio of 1:1:1) was used as the electrolyte. The CR2032 button battery was assembled in a glove box for electrochemical performance testing. The test voltage range was 2.5-4.5V, and the discharge capacity of the battery at 0.1C and 1C rates was tested respectively.

[0046] Example 1

[0047] (1) Add 5L of pure water to a stirring tank in advance (the amount of each raw material added in each subsequent step is based on the 5L of pure water added in step (1) as a reference for proportioning), add iron oxide, ammonium dihydrogen phosphate, lithium hydroxide and dispersant polyethylene glycol 800 under stirring, the amount of iron oxide, ammonium dihydrogen phosphate and lithium hydroxide added is 0.8 mol / L, 3.9 mol / L and 4.12 mol / L respectively, and the amount of polyethylene glycol 800 added is 30 g / L. After stirring evenly, add 0.8 mol / L of manganese tetraoxide, mix evenly, and obtain a precursor pre-made slurry;

[0048] (2) Add some pure water to the precursor pre-made slurry obtained in step (1) so that the solid content of the slurry reaches 45wt%; the total amount of pure water used in step (1) and step (2) is 5.5L.

[0049] (3) grinding the precursor slurry obtained in step (2) once under stirring until the particle size D50 reaches 0.4-0.45 μm to obtain a suspension containing lithium manganese iron phosphate precursor, transferring the suspension to another slurry barrel, and at the same time, rinsing the precipitated material at the bottom of the stirring tank with a small amount of pure water and transferring all of it to the slurry barrel;

[0050] (4) Add sucrose and organic phosphine scale inhibitor and corrosion inhibitor hydroxyethylidene diphosphonic acid to the slurry in the slurry barrel of step (3), based on the volume of pure water in step (1), the amount of sucrose added is 46g / L, the amount of hydroxyethylidene diphosphonic acid added is 0.12mol / L, and stir for 30min until completely dispersed and dissolved, and the viscosity of the resulting slurry is 220Pa·s; then transfer the slurry to the sand mill stirring tank for secondary grinding, control the particle size D50 between 0.3-0.32μm, and at this time, the particle distribution uniformity coefficient b in the sand mill slurry is less than 0.2. After grinding, the slurry is spray dried, and the spray drying air inlet temperature is controlled to 260°C and the air outlet temperature to 95°C to obtain a lithium manganese iron phosphate precursor.

[0051] (5) Sintering in nitrogen atmosphere: The lithium manganese iron phosphate precursor was transferred to a tubular furnace, replaced with nitrogen atmosphere, and then sintered in nitrogen atmosphere. The temperature was raised to 300°C at a heating rate of 2°C / min, and kept at that temperature for 1 hour. The temperature was raised to 500°C at a heating rate of 2°C / min, and kept at that temperature for 1 hour. The temperature was raised to 650°C at a heating rate of 2°C / min, and kept at that temperature for 8 hours. After cooling, the carbon-coated lithium manganese iron phosphate sample was obtained by air flow pulverization.

[0052] The lithium manganese iron phosphate positive electrode material prepared by the above method has a chemical formula of Li 1.03 Mn 0.6 Fe 0.4 (PO4) 1.035 , the powder compaction density is 2.38g / cm 3 The first discharge capacity at 0.1C rate is 155.6mAh / g; at 1C rate, the discharge capacity is 145.5mAh / g. The capacity retention rate after 100 cycles at 1C charge and discharge rate is 98.6%.

[0053] Example 2

[0054] (1) Add 5L of pure water to a stirring tank in advance (the amount of each raw material added in each subsequent step is based on the 5L of pure water added in step (1) as the benchmark for proportioning), add iron phosphate, phosphoric acid, lithium carbonate and dispersant polyvinyl alcohol under stirring, the amount of iron phosphate, phosphoric acid and lithium carbonate added is 1.2mol / L, 2.2mol / L and 2.02mol / L respectively, and the amount of polyvinyl alcohol added is 23g / L. After stirring evenly, add 2.8mol / L of manganese oxalate and mix evenly to obtain a precursor pre-made slurry;

[0055] (2) Add some pure water to the precursor pre-slurry obtained in step (1) so that the solid content of the slurry reaches 50wt%; the total amount of pure water used in step (1) and step (2) is 5.35L.

[0056] (3) grinding the precursor slurry obtained in step (2) once under stirring until the particle size D50 reaches 0.4-0.45 μm to obtain a suspension containing lithium manganese iron phosphate precursor, transferring the suspension to another slurry barrel, and at the same time, rinsing the precipitated material at the bottom of the stirring tank with a small amount of pure water and transferring all of it to the slurry barrel;

[0057] (4) Glucose and aminotri(methylenephosphonic acid) as an organic phosphine scale inhibitor and corrosion inhibitor are added to the slurry in the slurry barrel of step (3). Based on the volume of pure water in step (1), the amount of glucose added is 40 g / L, and the amount of aminotri(methylenephosphonic acid) added is 0.2 mol / L. After stirring until completely dispersed and dissolved, the viscosity of the resulting slurry is 560 Pa·s; then the slurry is transferred to the sand mill stirring tank for secondary grinding, and the particle size D50 is controlled between 0.3-0.32 μm. At this time, the particle distribution uniformity coefficient b in the sand mill slurry is less than 0.2. After the sand milling is completed, the slurry is spray dried, and the spray drying air inlet temperature is controlled to 250°C and the air outlet temperature to 90°C to obtain a lithium manganese iron phosphate precursor.

[0058] (5) Sintering in nitrogen atmosphere: The lithium manganese iron phosphate precursor was transferred to a tubular furnace, replaced with nitrogen atmosphere, and then sintered in nitrogen atmosphere. The temperature was raised to 250°C at a heating rate of 3°C / min, kept at this temperature for 2 hours, then raised to 450°C at a heating rate of 3°C / min, kept at this temperature for 2 hours, then raised to 680°C at a heating rate of 3°C / min, kept at this temperature for 7 hours. After cooling, the carbon-coated lithium manganese iron phosphate sample was obtained by air flow pulverization.

[0059] The lithium manganese iron phosphate positive electrode material prepared by the above method has a chemical formula of Li 1.01 Mn 0.7 Fe 0.3 PO4, powder compaction density is 2.4g / cm 3 The first discharge capacity at a rate of 0.1C is 154.8mAh / g; at a current rate of 1C, the discharge capacity is 144.5mAh / g; the capacity retention rate after 100 cycles at a charge and discharge rate of 1C is 98.4%.

[0060] Example 3

[0061] (1) Add 5L of pure water to a stirring tank in advance (the amount of each raw material added in each subsequent step is based on the 5L of pure water added in step (1) as a benchmark for proportioning), add ferrous oxalate, lithium dihydrogen phosphate, lithium carbonate and dispersant polyethylene glycol 6000 under stirring, the amount of ferrous oxalate, lithium dihydrogen phosphate, and lithium carbonate added is 1.2mol / L, 2.2mol / L and 0.16mol / L respectively, and the amount of dispersant added is 14g / L. After stirring evenly, add 1.2mol / L of manganese carbonate and mix evenly to obtain a precursor pre-slurry;

[0062] (2) Add some pure water to the precursor pre-made slurry obtained in step (1) so that the solid content of the slurry reaches 35wt%; the total amount of pure water used in step (1) and step (2) is 5.65L.

[0063] (3) grinding the precursor slurry obtained in step (2) once under stirring until the particle size D50 reaches 0.4-0.45 μm to obtain a suspension containing lithium manganese iron phosphate precursor, transferring the suspension to another slurry barrel, and at the same time, rinsing the precipitated material at the bottom of the stirring tank with a small amount of pure water and transferring all of it to the slurry barrel;

[0064] (4) Add ascorbic acid and organic phosphine scale inhibitor and corrosion inhibitor ethylenediaminetetramethylenephosphonic acid to the slurry in the slurry barrel of step (3), based on the volume of pure water in step (1), the amount of ascorbic acid added is 24g / L, and the amount of ethylenediaminetetramethylenephosphonic acid added is 0.044mol / L, and after stirring until completely dispersed and dissolved, the viscosity of the resulting slurry is 450Pa·s; then transfer the slurry to the sand mill stirring tank again, and perform secondary grinding treatment, control the particle size D50 between 0.3-0.32μm, and at this time, the particle distribution uniformity coefficient b in the sand mill slurry is less than 0.2. After grinding, the slurry is spray dried, and the spray drying inlet air temperature is controlled to 270°C and the outlet air temperature to 100°C to obtain a lithium manganese iron phosphate precursor.

[0065] (5) Sintering in nitrogen atmosphere: The lithium manganese iron phosphate precursor was transferred to a tubular furnace, and after nitrogen atmosphere replacement, nitrogen atmosphere sintering was performed. The temperature was raised to 350°C at a heating rate of 5°C / min, and kept at this temperature for 3 hours. The temperature was raised to 550°C at a heating rate of 5°C / min, and kept at this temperature for 3 hours. The temperature was raised to 730°C at a heating rate of 5°C / min, and kept at this temperature for 5 hours. After cooling, the carbon-coated lithium manganese iron phosphate sample was obtained by air flow pulverization.

[0066] The lithium manganese iron phosphate positive electrode material prepared by the above method has a chemical formula of Li 1.05 Mn 0.5 Fe 0.5 (PO4) 0.99 , the powder compaction density is 2.43g / cm 3 The first discharge capacity at a rate of 0.1C is 154.4mAh / g; at a current rate of 1C, the discharge capacity is 144.3mAh / g; the capacity retention rate after 100 cycles at a charge and discharge rate of 1C is 99.1%.

[0067] Example 4

[0068] (1) Add 5L of pure water to the stirring tank in advance (the amount of each raw material added in each subsequent step is based on the 5L of pure water added in step (1) as the benchmark for proportioning), add ammonium ferrous phosphate, phosphoric acid, lithium hydroxide and dispersant polyethylene glycol 6000 under stirring, the amount of ammonium ferrous phosphate, phosphoric acid, and lithium hydroxide added is 1 mol / L, 1.13 mol / L and 2.48 mol / L respectively, and the amount of dispersant added is 31 g / L. After stirring evenly, add 1.5 mol / L of manganese carbonate and mix evenly to obtain a precursor pre-made slurry;

[0069] (2) Add some pure water to the precursor pre-made slurry obtained in step (1) so that the solid content of the slurry reaches 35wt%; the total amount of pure water used in step (1) and step (2) is 5.05L.

[0070] (3) grinding the precursor slurry obtained in step (2) once under stirring until the particle size D50 reaches 0.4-0.45 μm to obtain a suspension containing lithium manganese iron phosphate precursor, transferring the suspension to another slurry barrel, and at the same time, rinsing the precipitated material at the bottom of the stirring tank with a small amount of pure water and transferring all of it to the slurry barrel;

[0071] (4) Add starch and organic phosphine scale inhibitor and corrosion inhibitor diethylene triamine penta methylene phosphonic acid to the slurry in the slurry barrel of step (3), based on the volume of pure water in step (1), the amount of starch added is 44 g / L, the amount of diethylene triamine penta methylene phosphonic acid added is 0.074 mol / L, and after stirring until completely dispersed and dissolved, the viscosity of the resulting slurry is 330 Pa·s; then transfer the slurry to the sand mill stirring tank again, and perform secondary grinding treatment, control the particle size D50 between 0.3-0.32 μm, and at this time, the particle distribution uniformity coefficient b in the sand mill slurry is less than 0.2. After grinding, the slurry is spray dried, and the spray drying air inlet temperature is controlled to 260°C and the air outlet temperature to 95°C to obtain a lithium manganese iron phosphate precursor.

[0072] (5) Sintering in nitrogen atmosphere: The lithium manganese iron phosphate precursor was transferred to a tubular furnace, replaced with nitrogen atmosphere, and then sintered in nitrogen atmosphere. The temperature was raised to 300°C at a heating rate of 3°C / min, kept at this temperature for 2 hours, then raised to 500°C at a heating rate of 3°C / min, kept at this temperature for 2 hours, then raised to 720°C at a heating rate of 3°C / min, kept at this temperature for 7 hours. After cooling, the carbon-coated lithium manganese iron phosphate sample was obtained by air flow pulverization.

[0073] The lithium manganese iron phosphate positive electrode material prepared by the above method has a chemical formula of Li 0.99 Mn 0.6 Fe 0.4 PO4, powder compaction density is 2.41g / cm 3The first discharge capacity at a rate of 0.1C is 153.7mAh / g; at a current rate of 1C, the discharge capacity is 143.5mAh / g; the capacity retention rate after 100 cycles at a charge and discharge rate of 1C is 98.5%.

[0074] Comparative Example 1

[0075] The lithium manganese iron phosphate positive electrode material is prepared by the same method as in Example 1, the main difference being that in step (4), no organic phosphorus scale inhibitor is added, and additional ammonium dihydrogen phosphate is used instead, and the molar amount of phosphorus in the additional ammonium dihydrogen phosphate is consistent with the molar amount of phosphorus in the organic phosphorus scale inhibitor in Example 1.

[0076] The lithium manganese iron phosphate positive electrode material prepared by the above method has a chemical formula of Li 1.03 Mn 0.6 Fe 0.4 (PO4) 1.035 , the powder compaction density is 2.31g / cm 3 The first discharge capacity at a rate of 0.1C is 145.8mAh / g; at a current rate of 1C, the discharge capacity is 134.8mAh / g; the capacity retention rate after 100 cycles at a charge and discharge rate of 1C is 95.6%.

[0077] Comparative Example 2

[0078] The lithium manganese iron phosphate positive electrode material was prepared by the same method as in Example 2, the main difference being that the organic phosphorus scale inhibitor and corrosion inhibitor aminotri(methylenephosphonic acid) was added and mixed evenly in step (1), and only the carbon source glucose was added in step (4).

[0079] The lithium manganese iron phosphate positive electrode material prepared by the above method has a chemical formula of Li 1.01 Mn 0.7 Fe 0.3 PO4, powder compaction density is 2.38g / cm 3 The first discharge capacity at a rate of 0.1C is 149.1mAh / g; at a current rate of 1C, the discharge capacity is 139.8mAh / g; the capacity retention rate after 100 cycles at a charge and discharge rate of 1C is 97.2%.

Claims

1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: (1) After the iron source, phosphorus source, lithium source and dispersant are uniformly stirred in water, a manganese source is added, and the mixture is uniformly mixed to obtain a precursor pre-slurry; (2) adjusting the solid content of the precursor pre-slurry to reach a target solid content A, wherein the target solid content A satisfies 30wt%≤A≤60wt%, preferably 35wt%≤A≤50wt%; preferably, the solid content of the precursor pre-slurry is adjusted by adding water; preferably, the amount of water used in step (1) accounts for 85-99% by volume of the total amount of water used in step (1) and step (2); (3) grinding the precursor slurry obtained in step (2) under stirring; (4) adding an organic phosphine scale inhibitor to the precursor slurry obtained in step (3) to dissolve the precursor slurry, preferably performing a secondary grinding treatment, and then drying the obtained slurry, sintering and pulverizing to obtain a lithium manganese iron phosphate positive electrode material; Wherein, a carbon source is added and dissolved in step (1), or a carbon source is added to the precursor slurry in step (4) and dissolved.

2. The preparation method according to claim 1, characterized in that: In step (1), the iron source is selected from one or more of ferric oxide, ferroferric oxide, ferrous phosphate, ferrous oxalate, and ammonium ferrous phosphate; The phosphorus source is one or more of iron phosphate, phosphoric acid, lithium dihydrogen phosphate, manganese hydrogen phosphate, and ammonium dihydrogen phosphate; The lithium source is one or more of lithium carbonate, lithium hydroxide, lithium phosphate and lithium dihydrogen phosphate; The dispersant is one or more of polyethylene glycol 800, polyethylene glycol 6000, methyl cellulose, polyvinyl alcohol and hexenyl bisstearamide; The manganese source is one or more of manganese dioxide, manganese carbonate, manganese oxalate, manganese sulfate, trimanganese tetraoxide, and manganese hydrogen phosphate.

3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the added iron element and the added manganese element is 0.11-1:1, and the ratio of the added molar amount of the lithium element to the sum of the added molar amounts of the iron element and the added manganese element is 0.9-1.1:1; Preferably, based on the volume of water added in step (1), the amount of the dispersant added is 5-50 g / L, preferably 10-35 g / L.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In step (3), the precursor slurry is subjected to the primary grinding treatment to a particle size D50 of 0.35-0.55 nm, preferably 0.4-0.45 μm.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The ratio of the sum of the molar amounts of phosphorus in the phosphorus source used in step (1) and the organic phosphine scale and corrosion inhibitor used in step (4) to the sum of the molar amounts of iron and manganese in the manganese source and the iron source is p, 0.99≤p≤1.05; Preferably, based on the volume of water used in step (1), the amount of the organic phosphine scale inhibitor added is 0.02-0.4 mol / L, preferably 0.04-0.2 mol / L.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The organic phosphine scale inhibitor contains more than two phosphonic acid groups, and the phosphorus atom is directly connected to the carbon atom. Preferably, the organic phosphine scale inhibitor includes one or more of hydroxyethylidene diphosphonic acid, aminotrimethylene phosphonic acid, diethylenetriamine penta (methylene phosphonic acid), and ethylenediaminetetramethylene phosphonic acid.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The carbon source includes one or more of glucose, sucrose, ascorbic acid, and starch; Preferably, based on the volume of water added in step (1), the amount of the carbon source added is 10-80 g / L, preferably 20-50 g / L.

8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (4), after the organic phosphine scale inhibitor is added and dissolved, the viscosity of the resulting slurry is 100-1000 Pa·s, preferably 200-600 Pa·s; Preferably, in step (4), the secondary grinding treatment is performed and the particle distribution uniformity coefficient b in the obtained slurry is less than 0.3, preferably less than 0.

2.

9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (4), the drying is carried out by spray drying, and the spray drying air inlet temperature is controlled to be 240-280°C, preferably 250-270°C; the air outlet temperature is controlled to be 85-105°C, preferably 90-100°C; Preferably, in step (4), the dried precursor is sintered in a nitrogen atmosphere, and the sintering conditions are preferably: heating to 250-350°C at a heating rate of 2-5°C / min, keeping warm for 1-3h, then heating to 400-550°C at a heating rate of 2-5°C / min, keeping warm for 1-3h, then heating to the target temperature at a heating rate of 2-5°C / min, and keeping warm for 5-12h; Preferably, the target temperature is 600-800°C, preferably 650-750°C.

10. A lithium iron manganese phosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 7; preferably, the chemical formula of the lithium iron manganese phosphate positive electrode material is Li x Mn y Fe z (PO4) p , where 0.9≤x≤1.1, 0.5≤y≤0.9, 0.1≤z≤0.5, 0.99≤p≤1.05, and y+z=1.